Antolín Jiménez Gamas en la construcción de lo mexicano - Llanos Jiménez, Fernando (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The research begins by locating identity elements of what is considered Mexican in the more than 700 elements of the archive of Antolín Jiménez Gamas throughout his life (1980 to 1975). Antolín was born in Tabasco during the Porfiriato he participated in the Mexican Revolution as a lieutenant colonel in Pancho Villa's Constitutionalist army then he became involved in Freemasonry becoming Grand Master 33rd degree and being a deputy four times with four different parties for Oaxaca. He worked in the Ministry of Finance as a Stamp Inspector he had a publishing house where he published tax laws. He was president of the National Association of Charros where he organized an army of charros to defend Mexico from a possible Nazi invasion. It historically locates the mechanisms and dissemination strategies that the Mexican State used to create and position that "Mexicanness" for decades responding to very specific ideological economic and political interests. Antolín participated in this identity imaginary embodying and promoting official graphic pictorial and audiovisual representations due to a series of historical circumstances and economic-political conveniences. Family archives as a bridge between the daily life of a Mexican and the great bronze narratives that were promoted from power.

La investigación parte de ubicar elementos identitarios de lo considerado mexicano, en los más de 700 elementos del archivo de Antolín Jiménez Gamas, a lo largo de su vida (1980 a 1975). Antolín nació en Tabasco durante el Porfiriato, participó en la Revolución Mexicana, como teniente coronel en el ejército Constitucionalista de Pancho Villa, después se involucró en la masonería llegando a ser Gran Maestro grado 33, y siendo diputado cuatro veces, con cuatro diferentes partidos, por Oaxaca. Trabajó en la Secretaría de Hacienda como inspector del Timbre, tuvo una editorial donde publicó leyes fiscales. Fue presidente de la Asociación Nacional de Charros, donde organizó un ejército de charros para defender a México de una posible invasión nazi. Ubica históricamente los mecanismos y estrategias de difusión que empleó el Estado mexicano para crear y posicionar esa "mexicaneidad" durante décadas, respondiendo a intereses ideológicos, económicos y políticos muy específicos. Antolín participó de dicho imaginario identitario, encarnando y promoviendo las representaciones gráficas, pictóricas y audiovisuales oficiales, por una serie de circunstancias históricas y conveniencias económico-políticas. Los archivos familiares como puente entre la vida cotidiana de un mexicano y las grandes narrativas de bronce que se promovieron desde el poder.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2023-1605; Regional continental; Identidad; Mexicano; Nacionalismo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16780